Proceedings of the 2nd International Congress on Sports Sciences Research and Technology Support 2014
DOI: 10.5220/0005080100970102
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue Participate in Lactate Utilization during Muscular Work

Abstract: In an experiment involving five healthy volunteers studied the dynamics of the skin temperature of the back and neck, combined with the dynamics of blood glucose and lactate during treadmill ramp test and 10 minutes of the recovery period. Skin temperature decreases in all cases at the beginning of the ramp test, but after reaching the anaerobic threshold temperature increases rapidly and reaches a maximum at the time of the refusal of work or shortly thereafter. Since the moment of reaching the anaerobic thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Whether beige and brown adipocytes could act as lactate metabolic sinks as recently proposed for succinate ( Mills et al, 2018 , 2021 ) or branched-chain amino acids ( Yoneshiro et al, 2019 ) remain to be demonstrated. This hypothesis may be supported by the positive correlation between plasma lactate and body temperature in five healthy volunteers subjected to physical exercise ( Son’kin et al, 2014 ). Interestingly, the rise in blood lactate levels precedes the rise in temperature.…”
Section: Reciprocal Relationships Between Lactate Metabolism and Adipose Tissue Biologymentioning
confidence: 91%
“…Whether beige and brown adipocytes could act as lactate metabolic sinks as recently proposed for succinate ( Mills et al, 2018 , 2021 ) or branched-chain amino acids ( Yoneshiro et al, 2019 ) remain to be demonstrated. This hypothesis may be supported by the positive correlation between plasma lactate and body temperature in five healthy volunteers subjected to physical exercise ( Son’kin et al, 2014 ). Interestingly, the rise in blood lactate levels precedes the rise in temperature.…”
Section: Reciprocal Relationships Between Lactate Metabolism and Adipose Tissue Biologymentioning
confidence: 91%